Proposition of a New Theoretical Model to Evaluate the Role of Social Network Sites in Driving Loyalty - Langaro, D.; Rita, P.; Salgueiro, M.F. (Proceedings of the Annual Conference of the Academy of Marketing,, 2012)
The Social Network Sites (SNS) represent a fast growing communication channel that allows brands to connect with their consumers in a one-to-one basis, launching the foundations of the potentially most expressive marketing relationship channel. In this context, a new theoretical approach is proposed, with the intent to determine the constructs that interplay between the brands in SNS and their users, focusing on understanding the impact over loyalty. In order to investigate this new area of knowledge, concepts are borrowed from Customer Relationship Management (CRM), Media Communications, Online Brand communities and New Technologies Adoption and are articulated into a unique conceptual model that extends customer relationship knowledge into the new territory of the Social Network Sites.